The prices in Europe of pomegranates and arils - Rymon D. (II International Symposium on the Pomegranate, 2012)
World pomegranates demand increased through the beginning of the 21st century, probably mainly due to the publication of research findings on the fruit's contribution to human health. A lack of dependable national statistics prevents us from estimating world trade. A paired time-series of price data by exporting and importing country in Europe is available, offering useful information to producers, traders and investors. The information allows an analysis of: (i) seasonality of fruit and aril prices by country of origin and European market; (ii) sensitivity of the trade to economic crises such as experienced in 2008; and (iii)estimation of supplier prices and comparison by hemispheres. The results are invaluable for producers andtraders, as well as regional and national plannners.
2. International Symposium on the Pomegranate, 2011/10/19-21, Madrid (Spain)